Review and Assessment of the Proposals for Design and Operation of Designated Chemical Agent Destruction Pilot Plants (DCAPP-Blue Grass II): Letter Report - National Research Council (The National Academies Press, 2006)
In 2002, the Army asked for proposals for a full-scale pilot plant to destroy chemical weapons at the Pueblo Chemical Depot and, in 2003, for a similar plant for the Blue Grass Army Depot. In both cases, the initial designs proved to be too costly, and redesigns were requested. At the same time, the Army asked the NRC to form committees to review and assess these proposals. This report focuses on the technical aspects, maturity, and schedule for the proposed full intermediate design for the Blue Grass facility, less the supercritical water oxidation process, which was reviewed in a previous report.

Letter Report of Review and Assessment of the Proposals for Design and Operation of Designated Chemical Agent Destruction Pilot Plants (DCAPP-Blue Grass) - National Research Council (The National Academies Press, 2006)
In 2002, the Army asked for proposals for a full-scale pilot plant to destroy chemical weapons at the Pueblo Chemical Depot and, in 2003, for a similar plant for the Blue Grass Army Depot. In both cases, the initial designs proved to be too costly, and redesigns were requested. At the same time, the Army asked the NRC to form committees to review and assess these proposals. This report focuses on the technical aspects, maturity, and schedule of the proposed modified design for the Pueblo facility.

Review and Assessment of the Proposals for Design and Operation of Designated Chemical Agent Destruction Pilot Plants (DCAPP-Pueblo): Letter Report - National Research Council (The National Academies Press, 2006)

Reusability of Facemasks During an Influenza Pandemic: Facing the Flu - Institute of Medicine (The National Academies Press, 2006)
Any strategy to cope with an influenza pandemic must be based on the knowledge and tools that are available at the time an epidemic may occur. In the near term, when we lack an adequate supply of vaccine and antiviral medication, strategies that rely on social distancing and physical barriers will be relatively more prominent as means to prevent spread of disease. The use of respirators and facemasks is one key part of a larger strategy to establish barriers and increase distance between infected and uninfected individuals. Respirators and facemasks may have a role in both clinical care and community settings. Reusability of Facemasks During an Influenza Pandemic: Facing the Flu answers a specific question about the role of respirators and facemasks to reduce the spread of flu: Can respirators and facemasks that are designed to be disposable be reused safely and effectively? The committee—assisted by outstanding staff—worked intensively to review the pertinent literature; consult with manufacturers, researchers, and medical specialists; and apply their expert judgment. This report offers findings and recommendations based on the evidence, pointing to actions that are appropriate now and to lines of research that can better inform future decisions.
Keywords: Health and Medicine

Is That Real?: Identification and Assessment of the Counterfeiting Threat for U.S. Banknotes - National Research Council (The National Academies Press, 2006)
A key mission of the Bureau of Engraving and Printing of the Department of the Treasury is the design and printing of U.S. banknotes. The BEP is responsible for producing easily recognizable currency that is difficult to counterfeit. In recent years, the bureau has recognized the modern information technology could lead to entirely new types of counterfeiting threats, and it has requested a number of studies by the NRC to assess these evolving threats. In this new request, the BEP asked the NRC to identify and evaluate significant emerging counterfeiting threats and to assess technologically feasible counterfeit-deterrent features for potential use in new designs. This first report provides an assessment of emerging threats including a wide range of digital imaging and printing techniques. It also presents an analysis of a systems approach to the counterfeiting threat. The second report will offer an evaluation of new banknote features to address these threats.
Keywords: Engineering and Technology

Visualizing Chemistry: The Progress and Promise of Advanced Chemical Imaging - National Research Council (The National Academies Press, 2006)
Scientists and engineers have long relied on the power of imaging techniques to help see objects invisible to the naked eye, and thus, to advance scientific knowledge. These experts are constantly pushing the limits of technology in pursuit of chemical imaging—the ability to visualize molecular structures and chemical composition in time and space as actual events unfold—from the smallest dimension of a biological system to the widest expanse of a distant galaxy. Chemical imaging has a variety of applications for almost every facet of our daily lives, ranging from medical diagnosis and treatment to the study and design of material properties in new products. In addition to highlighting advances in chemical imaging that could have the greatest impact on critical problems in science and technology, Visualizing Chemistry reviews the current state of chemical imaging technology, identifies promising future developments and their applications, and suggests a research and educational agenda to enable breakthrough improvements.
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

A Matter of Size: Triennial Review of the National Nanotechnology Initiative - National Research Council (The National Academies Press, 2006)
The National Nanotechnology Initiative (NNI) was created in 2000 to focus and coordinate the nanoscience and nanotechnology research and development (R&D) activities being funded by several federal agencies. The purpose of the NNI is to marshal these research activities in order to accelerate responsible development and deployment of nanotechnology for economic benefit and national security. To take stock of the progress of the NNI, Congress, in P. L. 108-153, the 21st Century Nanotechnology Research and Development Act, directed the National Research Council to carry out a review of the program every three years. This report presents the results of the first of those reviews, which addresses the economic impact of nanotechnology developments and provides a benchmark of U.S. R&D efforts relative to those undertaken by foreign competitors. In addition, the report offers an assessment of the current status of responsible development of nanotechnology and comments on the feasibility of molecular self-assembly.
Keywords: Engineering and Technology; Health and Medicine

Advanced Research Instrumentation and Facilities - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2006)
Keywords: Engineering and Technology

Strengthening Long-Term Nuclear Security: Protecting Weapon-Usable Material in Russia - National Research Council (The National Academies Press, 2006)
In July 2005, the National Academies released the report Strengthening Long-term Nuclear Security: Protecting Weapon-Usable Material in Russia. The report highlighted several obstacles in the transition from a U.S.-Russian cooperative program to a Russian-directed and Russian-funded fully indigenized program that will ensure the security of 600 tons of weapon-usable nuclear material at a level of international acceptability. Overcoming these obstacles requires an increased political commitment at a number of levels of the Russian Government to modern material protection, control, and accounting systems (MPC&A). Adequate resources must be provided to facilities where weapon-usable material is located for upgrading and maintaining MPC&A systems. Additionally, the technical security systems that are being installed through the cooperative program need to be fully embraced by Russian managers and specialists. The report recommends the establishment of a ten-year indigenization fund of about $500 million provided by Russia and its G-8 partners as a new mechanism for gradually shifting the financial burden of MPC&A to the Russian Government.
Keywords: Conflict and Security Issues

Identification of Promising Naval Aviation Science and Technology Opportunities - National Research Council (The National Academies Press, 2006)
The Department of Defense is developing the means to transform the nation’s armed forces to meet future military challenges. For the Navy and Marine Corps, this vision is encompassed in Naval Power 21. Many new war-fighting concepts will be needed to implement this vision, and the ONR has requested the NRC to identify new science and technology opportunities for new naval aviation capabilities to support those concepts. This report presents an assessment of what they imply for naval aviation, an analysis of some capabilities that, if developed, would make a significant contribution to realizing those concepts, and an identification of key technologies in which ONR could invest to achieve those capabilities. In particular, the report focuses on seven key capabilities: multispectral defense, unmanned air operations, hypersonic weapons delivery, fast-kill weapons, heavy-lift air transport, intelligent combat information management, and omniscient intelligence.
Keywords: Space and Aeronautics

Safety and Security of Commercial Spent Nuclear Fuel Storage: Public Report - National Research Council (The National Academies Press, 2006)
In response to a request from Congress, the Nuclear Regulatory Commission and the Department of Homeland Security sponsored a National Academies study to assess the safety and security risks of spent nuclear fuel stored in cooling pools and dry casks at commercial nuclear power plants. The information provided in this book examines the risks of terrorist attacks using these materials for a radiological dispersal device. Safety and Security of Commercial Spent Nuclear Fuel is an unclassified public summary of a more detailed classified book. The book finds that successful terrorist attacks on spent fuel pools, though difficult, are possible. A propagating fire in a pool could release large amounts of radioactive material, but rearranging spent fuel in the pool during storage and providing emergency water spray systems would reduce the likelihood of a propagating fire even under severe damage conditions. The book suggests that additional studies are needed to better understand these risks. Although dry casks have advantages over cooling pools, pools are necessary at all operating nuclear power plants to store at least the recently discharged fuel. The book explains it would be difficult for terrorists to steal enough spent fuel to construct a significant radiological dispersal device.
Keywords: Conflict and Security Issues; Environment and Environmental Studies

Midsize Facilities: The Infrastructure for Materials Research - National Research Council (The National Academies Press, 2006)
Most of the instruments now used for materials research are too complex and expensive for individual investigators to own, operate, and maintain them. Consequently, they have become increasingly consolidated into multi-user, small to midsized research facilities, located at many sites around the country. The proliferation of these facilities, however, has drawn calls for a careful assessment of best principles for their operation. With support from the Department of Energy and the National Science Foundation, the NRC carried out a study to characterize and discuss ways to optimize investments in materials research facility infrastructure with attention to midsize facilities. This report provides an assessment of the nature and importance of mid-sized facilities, their capabilities, challenges they face, current investment, and optimizing their effectiveness.
Keywords: Engineering and Technology

A Review of United States Air Force and Department of Defense Aerospace Propulsion Needs - National Research Council (The National Academies Press, 2006)
Rocket and air-breathing propulsion systems are the foundation on which planning for future aerospace systems rests. A Review of United States Air Force and Department of Defense Aerospace Propulsion Needs assesses the existing technical base in these areas and examines the future Air Force capabilities the base will be expected to support. This report also defines gaps and recommends where future warfighter capabilities not yet fully defined could be met by current science and technology development plans.
Keywords: Conflict and Security Issues; Space and Aeronautics

Asbestos: Selected Cancers - Institute of Medicine (The National Academies Press, 2006)
In conjunction with drafting comprehensive legislation concerning compensation for health effects related to asbestos exposure (the Fairness in Asbestos Injury Act), the Senate Committee on the Judiciary directed the Institute of Medicine to assemble the Committee on Asbestos: Selected Health Effects. This committee was charged with addressing whether asbestos exposure is causally related to adverse health consequences in addition to asbestosis, mesothelioma, and lung cancer. Asbestos: Selected Cancers presents the committee&#39s comprehensive distillation of the peer-reviewed scientific and medical literature regarding association between asbestos and colorectal, laryngeal, esophageal, pharyngeal, and stomach cancers.
Keywords: Health and Medicine; Environment and Environmental Studies

To Recruit and Advance: Women Students and Faculty in Science and Engineering - National Research Council (The National Academies Press, 2006)
Although more women than men participate in higher education in the United States, the same is not true when it comes to pursuing careers in science and engineering. To Recruit and Advance: Women Students and Faculty in Science and Engineering identifies and discusses better practices for recruitment, retention, and promotion for women scientists and engineers in academia. Seeking to move beyond yet another catalog of challenges facing the advancement of women in academic science and engineering, this book describes actions actually taken by universities to improve the situation for women. Serving as a guide, it examines the following: Recruitment of female undergraduates and graduate students. Ways of reducing attrition in science and engineering degree programs in the early undergraduate years. Improving retention rates of women at critical transition points—from undergraduate to graduate student, from graduate student to postdoc, from postdoc to first faculty position. Recruitment of women for tenure-track positions. Increasing the tenure rate for women faculty. Increasing the number of women in administrative positions. This guide offers numerous solutions that may be of use to other universities and colleges and will be an essential resource for anyone interested in improving the position of women students, faculty, deans, provosts, and presidents in science and engineering.
Keywords: Education; Behavioral and Social Sciences

Hearing Loss Research at NIOSH: Reviews of Research Programs of the National Institute for Occupational Safety and Health - Institute of Medicine; National Research Council (The National Academies Press, 2006)
The National Institute for Occupational Safety and Health (NIOSH) was established by the Occupational Safety and Health Act of 1970 (U.S. Congress, 1970). Today the agency is part of the Centers for Disease Control and Prevention of the U.S. Department of Health and Human Services. NIOSH is charged with the responsibility to "conduct . . . research, experiments, and demonstrations relating to occupational safety and health" and to develop "innovative methods, techniques, and approaches for dealing with [those] problems" (U.S. Congress, 1970). Its research targets include identifying criteria for use in setting worker exposure standards and exploring new problems that may arise in the workplace. Prevention of occupational hearing loss has been part of the NIOSH research portfolio from the time the agency was established. A principal cause of occupational hearing loss is the cumulative effect of years of exposure to hazardous noise. Exposure to certain chemicals with or without concomitant noise exposure may also contribute to occupational hearing loss. Hearing loss may impede communication in the workplace and contribute to safety hazards. Occupationally acquired hearing loss may also have an adverse effect on workers' lives beyond the workplace. No medical means are currently available to prevent or reverse it, although hearing aids are widely used and research on other treatments is ongoing. Occupational hearing loss is a serious concern, although the number of workers affected is uncertain. In September 2004, NIOSH requested that the National Academies conduct reviews of as many as 15 NIOSH programs with respect to the impact and relevance of their work in reducing workplace injury and illness and to identify future directions that their work might take. The Hearing Loss Research Program was selected by NIOSH as one of the first two programs to be reviewed. Hearing Loss Research at NIOSH examines the following issues for the Hearing Loss Research Program: (1) Progress in reducing workplace illness and injuries through occupational safety and health research, assessed on the basis of an analysis of relevant data about workplace illnesses and injuries and an evaluation of the effect that NIOSH research has had in reducing illness and injuries, (2) Progress in targeting new research to the areas of occupational safety and health most relevant to future improvements in workplace protection, and (3) Significant emerging research areas that appear especially important in terms of their relevance to the mission of NIOSH.
Keywords: Health and Medicine; Industry and Labor

State and Federal Standards for Mobile-Source Emissions - National Research Council (The National Academies Press, 2006)
Emissions from mobile sources contribute significantly to air pollution in the United States. Such sources include cars and light- and heavy-duty trucks; diesel-powered cranes, bulldozers, and tractors; and equipment such as lawnmowers that run on small gasoline engines. The role of state versus federal government in establishing mobile-source emissions standards is an important environmental management issue. With this in mind, Congress called on EPA to arrange an independent study of the practices and procedures by which California develops separate emissions standards from the federal government and other states choose to adopt the California standards. The report provides an assessment of the scientific and technical procedures used by states to develop or adopt different emissions standards and a comparison of those policies and practices with those used by EPA. It also considers the impacts of state emissions standards on various factors including compliance costs and emissions. The report concludes that, despite the substantial progress in reducing emissions from mobile sources nationwide, more needs to be done to attain federal air-quality standards in many parts of the country. Additionally, California should continue its pioneering role in setting emissions standards for cars, trucks, and off-road equipment.
Keywords: Transportation and Infrastructure; Environment and Environmental Studies

Learning to Think Spatially - National Research Council (The National Academies Press, 2006)
Learning to Think Spatially examines how spatial thinking might be incorporated into existing standards-based instruction across the school curriculum. Spatial thinking must be recognized as a fundamental part of K–12 education and as an integrator and a facilitator for problem solving across the curriculum. With advances in computing technologies and the increasing availability of geospatial data, spatial thinking will play a significant role in the information-based economy of the twenty-first century. Using appropriately designed support systems tailored to the K–12 context, spatial thinking can be taught formally to all students. A geographic information system (GIS) offers one example of a high-technology support system that can enable students and teachers to practice and apply spatial thinking in many areas of the curriculum.
Keywords: Education

Drinking Water Distribution Systems: Assessing and Reducing Risks - National Research Council (The National Academies Press, 2006)
Protecting and maintaining water distributions systems is crucial to ensuring high quality drinking water. Distribution systems -- consisting of pipes, pumps, valves, storage tanks, reservoirs, meters, fittings, and other hydraulic appurtenances -- carry drinking water from a centralized treatment plant or well supplies to consumers’ taps. Spanning almost 1 million miles in the United States, distribution systems represent the vast majority of physical infrastructure for water supplies, and thus constitute the primary management challenge from both an operational and public health standpoint. Recent data on waterborne disease outbreaks suggest that distribution systems remain a source of contamination that has yet to be fully addressed. This report evaluates approaches for risk characterization and recent data, and it identifies a variety of strategies that could be considered to reduce the risks posed by water-quality deteriorating events in distribution systems. Particular attention is given to backflow events via cross connections, the potential for contamination of the distribution system during construction and repair activities, maintenance of storage facilities, and the role of premise plumbing in public health risk. The report also identifies advances in detection, monitoring and modeling, analytical methods, and research and development opportunities that will enable the water supply industry to further reduce risks associated with drinking water distribution systems.
Keywords: Environment and Environmental Studies